Meningkatkan Aktivitas dan Hasil Belajar Siswa Menggunakan Model Crystal Di SDN Kelayan Dalam 7 Banjarmasin - Rahma Dewi Astuti; Noorhapizah (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The research problem is the low level of activity that affects students' learning outcomes. This is because learning activities are not focused on student activity; there aren't any students who make opinions and have not understood the concept of the material. Applying the CRYSTAL model is an attempt to solve the problem. The purpose of research is to determine teacher activity, student activity improvement, and student learning outcomes. Research uses the type of class action research, and the subject is 28 students. The data collected in the research is both qualitative and quantitative, with qualitatively derived data from the activities of teachers and students observed and quantifiable data from student learning outcomes measured through written tests. The data analysis used in the research is cross-tabulation analysis. Research results show that teacher activity meeting 1–4 increased getting 100% criteria very well. Student activity meeting 1 to 4 increased earning 93% of the criteria; almost all students were very active. So affecting the increase in learning outcomes, students meeting 1 to 4 obtained 99% of the criteria; almost all students passed. The research concluded that the learning process of mathematics using the CRYSTAL model can improve teacher activity, student activity, and learning outcomes.